An observational study on prevalence and determinants of PCOS in women presenting with acne vulgaris to a tertiary care hospital in North India - Chandra, Mini; Garg, Palak; Vats, Koshinder; Tibrewal, Abhishek O. (International Journal Of Community Medicine And Public Health, 2021)
Background: Acne vulgaris is an inflammatory disease of pilosebaceous gland that usually affects people from puberty to young adulthood. Apart from being a dermatological condition, acne is now recognised to be related to a plethora of systemic disorders, notably endocrinal abnormalities, like Polycystic Ovarian Syndrome (PCOS). We conducted this study with the aim of finding the prevalence and determinants of PCOS among patients presenting with acne vulgaris. Methods: In this prospective observational study, 100 women were selected who presented with acne, to the out-patient dermatology department of our hospital. The study subjects were 14 to 36 years old, non-pregnant females, who agreed to be a part of the study. PCOS was diagnosed using Rotterdam criteria. Statistical software (SPSS version 22) was used for the statistical analyses. Results: Out of the 100 study subjects, 81 (81%) had PCOS and 19 (19%) did not. The subjects who had PCOS were older (Median of 22 years vs 20 years), higher FSH levels (Median of 5.8 vs 3.2), higher LH/FSH ratio (Median of 0.7 vs 0.6), and higher DHEA levels (Median of 285.5 vs 160.3), though these differences were not statistically significant. The PCOS group was more likely to be suffering from irregular menses (OR, 1.51; 95% CI: 0.5-4.5, p value 0.46), weight gain (OR, 1.02; 95% CI: 0.37-2.7, p value 0.97), and hirsutism (OR, 1.17; 95% CI: 0.43 - 3.24), as compared to the non-PCOS group. However, PCOS was not significantly associated with age, duration of acne, fasting blood sugar levels, HOMA-IR, or levels of hormones like FSH, LH, Testosterone, DHEA, and Insulin. Conclusions: The study concludes a high prevalence of PCOS among acne patients. All women with acne should be considered for underlying PCOS and asked about their menstrual patterns and examined for other sign of hyperandrogenism.